Adherence to Intermittent Preventive Treatment of Malaria in Pregnancy with Sulfadoxine–Pyrimethamine and Associated Factors: A Cross-Sectional Survey in Benin’s Public Hospitals. - AGUEMON, BADIROU DIN OWOLADÉ OTONIKOU; OUENDO, Edgard-Marius; Damien, Georgia (My University, 2018)
Abstract: Background: Gestational malaria is a public health problem, thus responsible for morbidity and mortality risk to both the foetus and the mother. The intermittent preventive treatment with sulfadoxine-pyrimethamine during pregnancy (IPTp-SP) is one of the strategies recommended by the WHO to prevent this pathology and its consequences during pregnancy. In Benin, the adherence rate remains below the programmatic targets. This study aimed to identify the factors associated to the adherence to at least two IPTp-SP doses for postpartum women of the University Hospital HKM of Cotonou (CNHU-HKM) and the University Hospital for Mother and Child (CHU-MEL) of Cotonou. Methods: A cross-sectional hospital-based study was conducted over a 3-month-period, from July to September 2015 in the field of gynaecology and obstetrics departments of the two hospitals. All the mothers who had delivered and were still hospitalized at the time of the study were enrolled. Results: During their last pregnancy, 63.11% of women had taken at least two doses of IPTp-SP. Four determinants of adherence to the two IPTp-SP doses were associated to the adherence to two doses of IPTp-SP: i) adequate knowledge of the number of doses of SP to be taken during the pregnancy (p value<0.0001), ii) participation in communication for social and behavioural change on IPTp-SP (pvalue< 0.0001), iii) adequate knowledge of the number of tablets per dose of SP (p-value=0.0100), and iv) comprehensive knowledge of malaria prevention measures during pregnancy (p-value=0.0200). Conclusion: Raising and improving women's knowledge on malaria are necessary to achieve ITPp-SP adherence. Particular emphasis should therefore be placed on communication for social and behavioural change for pregnant women, family decision-makers, community leaders and healthcare workers.
Keywords: Malaria; Intermittent preventive treatment; Pregnancy; Social and behaviour change communication; IPTp-; SP adherence; Postpartum women.